2020
DOI: 10.1038/s41467-020-20030-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based cross-classifications reveal conserved spatial behaviors within tumor histological images

Abstract: Histopathological images are a rich but incompletely explored data type for studying cancer. Manual inspection is time consuming, making it challenging to use for image data mining. Here we show that convolutional neural networks (CNNs) can be systematically applied across cancer types, enabling comparisons to reveal shared spatial behaviors. We develop CNN architectures to analyze 27,815 hematoxylin and eosin scanned images from The Cancer Genome Atlas for tumor/normal, cancer subtype, and mutation classifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 67 publications
1
104
0
1
Order By: Relevance
“…In addition to applying deep learning to a single cancer type, researchers have shown that a single neural network may be applied across different tissues. Noorbakhsh et al trained a neural network to predict the mutation status of TP53 using patients with a single cancer type, and showed that the model could generalise to other tissues with comparable results to self-cohort models [44]. For example, a model trained on breast cancer data achieved AUCs of 0.72, 0.71 and 0.67 on lung adenocarcinoma, stomach adenocarcinoma and bladder urothelial carcinoma test sets, respectively, while also achieving similar performance on the lung adenocarcinoma cases to Coudray et al [34].…”
Section: Predicting Mutationsmentioning
confidence: 99%
“…In addition to applying deep learning to a single cancer type, researchers have shown that a single neural network may be applied across different tissues. Noorbakhsh et al trained a neural network to predict the mutation status of TP53 using patients with a single cancer type, and showed that the model could generalise to other tissues with comparable results to self-cohort models [44]. For example, a model trained on breast cancer data achieved AUCs of 0.72, 0.71 and 0.67 on lung adenocarcinoma, stomach adenocarcinoma and bladder urothelial carcinoma test sets, respectively, while also achieving similar performance on the lung adenocarcinoma cases to Coudray et al [34].…”
Section: Predicting Mutationsmentioning
confidence: 99%
“…Javad et al. systematically used CNNs on 23 cancer types for tasks including tumor versus normal and cancer subtype classifications as well as predicting the presence of TP53 mutations ( Noorbakhsh, et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Representative examples of CNN-based models for pathology applications include tumor/benign classification (23)(24)(25)(26)(27), predicting mutations in key genes (24,27,28), cancer subtype classification and morphology analysis (23,30), and treatment outcome prediction (31,32). These models have shown impressive performance, demonstrating that subtle molecular features of cancer may be discernible from H&E images.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growth in machine learning approaches, especially deep learning, in the field of pathology (19). These typically utilize Convolutional Neural Network (CNN) architectures, such as AlexNet (20), GoogleNet (21), or ResNet (22), etc., pre-trained on generic images, and then fine-tune them by re-training the last layers for a specific classification task. This approach is typically referred to as "transfer-learning".…”
mentioning
confidence: 99%